Detailed MRI-Anatomic Study of the Lateral Epicondyle of the Elbow and Its Tendinous and Ligamentous Attachments in Cadavers - Zoner, Cristiane Soares [UNIFESP] (2010)
OBJECTIVE. the objective of our study was to document discrete bone landmarks in the lateral epicondyle of the humerus that represent the footprints of those tendons and ligaments that attach to it using MRI-anatomic correlation in cadavers.MATERIALS and METHODS. Thirty-three dried humeral specimens were inspected to document bone landmarks in the lateral epicondyle. MRI with anatomic correlation was performed in 10 additional cadaveric elbows. the locations of the tendinous and ligamentous attachments to the lateral epicondyle were determined with respect to the same osseous landmarks.RESULTS. the surface of the lateral epicondyle ranged from a flat surface to a surface with up to six discrete landmarks: superior tubercle, anterior tubercle, posterior tubercle, intertubercular sulcus, rough area surrounding the tubercles, and epicondylar ridge. the radial collateral ligament attached to the superior aspect of the intertubercular sulcus and inferior aspect of the superior tubercle and was indistinguishable from the attachment of the lateral ulnar collateral ligament. the extensor carpi radialis brevis, extensor digitorum communis, and extensor digiti minimi had a common origin in the superior aspect of the lateral epicondyle. the extensor carpi ulnaris tendon arose from the posteroinferior aspect of the lateral epicondyle.CONCLUSION. Our investigation documents osseous landmarks that are useful in the identification of the footprints of the tendons and ligaments that attach to the lateral epicondyle. Knowledge of these structures contributes to correct interpretation of MR images in persons with tendinous and ligamentous abnormalities in this region.